2018
DOI: 10.1332/204080518x15199961331635
|View full text |Cite
|
Sign up to set email alerts
|

Local civil society regimes: liberal, corporatist and social democratic civil society regimes in Swedish metropolitan cities

Abstract: Academic debates on the role and position of civil society organisations (CSOs) in welfare states largely refer to policies and practices outlined at the national level. They therefore fail to recognise variations within nations. Based on a comparative case study of three Swedish metropolitan cities, this article illustrates the importance of local, contextualised analyses. Through the concept of local civil society regimes, the study identifies three regime types, namely liberal, corporatist and social democr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The other cases, although they do also reflect national policy structures and discourses such as protective 'youth welfare' (Germany), corporatism and de/centralization (France), and controlling youth as a problem under conditions of austerity (UK), reveal the manifold ways in which national policies are interpreted and implemented differently at the local level. These depend upon local constellations of governance and governmentality (Arvidson et al, 2018;Stenson, 2008). Apart from the influence and power of formal settings of youth participation, the resources, the different role of adults involved and the rules through which recognition and power are conditioned also contribute to different processes of young people's subjectivation (Butler, 2015).…”
Section: From Local Constellations To Regimes Of Youth Participation?mentioning
confidence: 99%
See 2 more Smart Citations
“…The other cases, although they do also reflect national policy structures and discourses such as protective 'youth welfare' (Germany), corporatism and de/centralization (France), and controlling youth as a problem under conditions of austerity (UK), reveal the manifold ways in which national policies are interpreted and implemented differently at the local level. These depend upon local constellations of governance and governmentality (Arvidson et al, 2018;Stenson, 2008). Apart from the influence and power of formal settings of youth participation, the resources, the different role of adults involved and the rules through which recognition and power are conditioned also contribute to different processes of young people's subjectivation (Butler, 2015).…”
Section: From Local Constellations To Regimes Of Youth Participation?mentioning
confidence: 99%
“…This ‘softness’ and particularities make cross-country comparative analysis difficult. Andreotti et al (2012) have shown and convincingly argued that comparing social policies at the local levels—different from national welfare states—faces difficulties in developing typologies due to the complexity of relationships between single policy decision processes, actor relationships, organizational cultures and users of youth policies (Arvidson et al, 2018; Jensen & Lolle, 2013; Mingione et al, 2002). If we still refer to regimes, we first of all refer to the theoretical way in which they conceptualize the complex constellations of governing the relationship between individuals and society.…”
Section: Comparative Research On Youth Policy and Youth Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, following the literature on local civil society regimes, we can assume that the two scenarios can have different relevance depending on the municipality (Arvidson et al 2018;Johansson et al 2015). According to this literature, there is a variation between municipalities regarding grants and payments performed by civil society organizations.…”
Section: Two Scenariosmentioning
confidence: 99%
“…The Action Plan served to further formalise a model that had developed over the year 2014, according to which support for 'vulnerable EU citizens' is organised through public-private partnerships with Christian charities. This reliance on the civil society sector is in itself nothing new: There is a fairly longstanding tradition in many Swedish municipalities, including Malmö, of organising homelessness services through hybrid institutions and partnerships between the public sector and CSOs (Arvidson, Johansson, Johansson, & Nordfeldt, 2018;Nordfeldt, 1999 During the winter of 2014/2015, the City of Malmö also opened the first overnight facility specifically geared towards street-homeless EU citizens. In previous years, the municipality had not provided any such facilities as it was assumed that most EU citizens would return home during the winter months (Paulsson, 2015) .…”
Section: Local Policies and Initiatives To Provide Shelter And Servicesmentioning
confidence: 99%